Optimisme pada Wanita Lanjut Usia yang Mengalami Kematian Pasangan Hidup - Fetty Nur Tiyaningsih; Santi Sulandari (Psympathic : Jurnal Ilmiah Psikologi, 2021)
This study aims to describe the problem, the form of optimism, and influential factors of optimism on elder people who experienced loss of the loved ones. This study used quantitative-phenomenology with the data collection used semi-structured interviews. The informants were recruited using purposive sampling technique with the total of five elder widows in Sragen. The data was analyzed using thematic analysis. The information record, member-checking, and data delivery were implemented to maintain data validity and objectivity. The results show that the problem after the loss including the feel of loss, decrease of economic condition, loneliness, and health degradation. In overcoming the problems, they were not easily give up and despair, always accept the changes, and have a good hope on their life events. These ability occured because of the willingness to bounce back, attention and support from the closest people. The importance of optimism lead to a motivation from inside the elder widow to rise up and have positive thoughts on life problems they experienced.